Kajian Sosiologi Sastra Dalam Cerpen “Di Persimpangan Pantura” Karya Tantri Pranash - Eny Junyanti (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2024)
A short story is a literary work in the form of prose that contains a conflict with a short, focused solution only on one incident or story. The most important thing in a short story is to reveal the author's events and ideas in such a way that the reader can understand and enjoy it. The short story "At the Pantura Crossing" by Tantri Pranash published on Kompas.com on December 11 2011 is a short story that represents social reality in the region Pantura (North Coast of Java). Precisely in the Patokbeusi area which is a prostitution area, which contains the dynamics of relationships between characters, social conflicts, and the values upheld in the film local community. The aim of this research is to analyze the content of Tantri Pranash's short story "In Pantura Intersection” using a literary sociology approach. In literary sociology, Literary works are seen as a reflection of social life and cannot be separated from consideration elements of fiction and social aspects in social life. This means studying literary sociology the relationship between literary works and people in society, as well as social processes. Method The research used in this research is a qualitative descriptive research method. With using reading and note-taking techniques as data collection techniques. Short story research results Tantri Pranash ``At the Panthura Junction'' contains (1) economic aspects, (2) aspects culture, (3) social aspects, and (4) moral aspects. These results explain that literary works reflect community life.